ANTIFUNGAL UTILIZATION AND OUTCOME EVALUATION IN A TERTIARY HOSPITAL - Islahudin, Farida; Yip, Lee Ann (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: The risk of fungal infection is one of the many concerns of patients admitted for chronic illness. The increase in fungal infection causes excessive morbidity and mortality. Despite the use of antifungals, the outcome of patients remains challenging. The study was performed to identify factors affecting the outcome of antifungal use. Methods: A retrospective study was carried out in a local tertiary hospital for the past 1 year. Patients prescribed antifungals were included. Results: A total of 145 patients who had been prescribed with antifungal agents within the past year were included in the study. It was noted that patients infected with fungi were mostly elderly patients (n=83, 57.2%). A majority of the patients (n=67, 46.2%, p<0.001) were diagnosed with or suspected to have systemic fungal infection compared to urinary fungal infection (n=31, 21.4%), oral fungal infection (n=20, 13.8%), pulmonary fungal infection (n=19, 13.1%), and others (n=8, 5.5%). As such, intravenous antifungal was the most commonly prescribed dosage form (n=88, 60.7%, p<0.001). The mortality rate of patients with fungal infection was 35.9% (n=52). No significant factors were observed to affect the clinical outcome of patients. However, factors affecting survival outcome in patients treated for fungal infection were targeted treatment (p=0.036), less number of medications (p<0.001), and a higher number of antifungals prescribed (p=0.010). Conclusion: A more comprehensive review of medication is required to ensure appropriate treatment is given to patients with fungal infection. Keywords: Antifungal, Fungal infection, Outcome.